2022
DOI: 10.1007/s10198-022-01443-z
|View full text |Cite
|
Sign up to set email alerts
|

The attractiveness of jobs in the German care sector: results of a factorial survey

Abstract: The skilled labour shortage in nursing is an issue not unique to Germany. Unattractive characteristics of nursing jobs are one reason for the low supply in nursing personnel. In our study, we analyse the influence of job characteristics on the attractiveness of nursing jobs. We address this issue via factorial survey analysis, an experimental method particularly suited to assessing personal opinions and less prone to social desirability bias than standard interview methods. Around 1300 (current and former) nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…[39] Importantly, there is some evidence that appreciation is the most important factor influencing job satisfaction [40] and that the team atmosphere and having time for patients may matter more than material rewards. [19] The students in this study suggest enhancing nursing appreciation in society by increasing realistic information about nursing. For example, this image could be accomplished through informative videos or real-life case studies on social media and by sharing clients' positive experiences of effective nursing care.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[39] Importantly, there is some evidence that appreciation is the most important factor influencing job satisfaction [40] and that the team atmosphere and having time for patients may matter more than material rewards. [19] The students in this study suggest enhancing nursing appreciation in society by increasing realistic information about nursing. For example, this image could be accomplished through informative videos or real-life case studies on social media and by sharing clients' positive experiences of effective nursing care.…”
Section: Discussionmentioning
confidence: 83%
“…[18] A recent study in Germany revealed that enormous wage raises would be needed to yield higher attractiveness gains than the so-called soft factors, or time for patients and atmosphere within the team. [19] Besides these intrinsic factors, extrinsic factors, for example, job security and employment opportunities [20] and contract duration, [19] influence career choice significantly.…”
Section: Introductionmentioning
confidence: 99%
“…We perceive a lack of time for patient care, thereby highlighting a persistent systemic issue. The NEXT study [24] and other German studies [7,31,32,49] indicate that job satisfaction in nursing can be improved, primarily in time for patients, work-life balance, and workload. Our study also reflects a gratification crisis, which is evidenced by dissatisfaction with payment and appreciation [15,25].…”
Section: Interpretation Of Our Main Findingsmentioning
confidence: 97%
“…However, not all influential factors, like leadership, were included in our model due to limited effect sizes. Effective leadership is still crucial in nurses' retention decisions, as evidenced by other studies [10,24,32,49].…”
Section: Debate Regarding the Answer Of Rq 3: Factors To Nurses Reten...mentioning
confidence: 97%
See 1 more Smart Citation